HIV prevalence among blood donors in a blood bank in Maranhão - Pereira, Ana Maria B.; Nascimento, Flávia R.F. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: in the beggining of HIV infection, blood or blood-derived transfusion was the most important via of infection. Since 1985, blood isanalysed with ELISA assay to anti- HIV detection to select the healthy donors. Objective: to determine the prevalence of anti-HIV antibodies inblood donors of HEMOMAR. Methods: we did a retrospective study where we revised the serologic results from all donors in the period of Januaryto July of 2002. The tests were made in HEMOMAR using ELISA assay. Results:the result obtained showed that there were 21.163 negative donorsand 267 positive ones, with a prevalence of 1,25% of positive tests to anti-HIV. Conclusion: we conclude that despite of the trials of blood donors, itis still big the number of positive cases to HIV in blood center of Maranhão, what is a risk factor to contamination.